2020
DOI: 10.3389/fnana.2020.584266
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Dissection of the Fetal Brain

Abstract: Neuroplasticity is a complex process of structural and functional reorganization of brain tissue. In the fetal period, neuroplasticity plays an important role in the emergence and development of white matter tracts. Here, we aimed to study the architecture of normal fetal brains by way of Klingler's dissection. Ten normal brains were collected from in utero deceased fetuses aged between 13 and 35 gestational weeks (GW). During this period, we observed modifications in volume, shape, and sulci configuration. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 57 publications
2
35
0
Order By: Relevance
“…Their results showed that the periinsular portion of SLF, corresponding to our SLF III segment and AF, can be identi ed by dissection at 14 weeks. Then the newer bers always emerge in more super cial positions with the gestational age increasing and formed a more super cial component of SLF (Horgos et al 2020), corresponding to our SLF II segment. The sequence of development in periinsular area from ventral to the dorsal direction supported our quantitative analysis results, that is, ventral SLF III is more mature than dorsal SLF II in human neonatal period.…”
Section: Quantitative Analysis Of Slf Subcomponentsmentioning
confidence: 85%
“…Their results showed that the periinsular portion of SLF, corresponding to our SLF III segment and AF, can be identi ed by dissection at 14 weeks. Then the newer bers always emerge in more super cial positions with the gestational age increasing and formed a more super cial component of SLF (Horgos et al 2020), corresponding to our SLF II segment. The sequence of development in periinsular area from ventral to the dorsal direction supported our quantitative analysis results, that is, ventral SLF III is more mature than dorsal SLF II in human neonatal period.…”
Section: Quantitative Analysis Of Slf Subcomponentsmentioning
confidence: 85%
“…These rotational movements of the hippocampal rudiment occur due to gradients induced by genetic expression, the fact that is key in some malformations ( 8 ). The formation of the forebrain fissures is also impacted by the development of the ventricles, which behaves as an external mechanical force rather than an internal force ( 8 , 10 , 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, and although the horizontal segment is widely similar in humans and monkeys, the vertical segment is missed in the latter. The frontotemporal connections are the first ones to be identified during the embryogenesis (around the 17 gw), while the parietal branches appear a few weeks later during the development (20 gw) ( 11 ). SLF II and III posterior extensions to the angular and supramarginal gyri show a slight inferolateral curve, probably given by the inferior parietal lobe ventrolateral movement during the CNS development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of the CC begins with the projection of pioneer fibers from the cingulate and rostrolateral cortices [ 25 , 26 , 27 ] at around the 12th week of gestation (GW) in humans, followed by formation of the genu [ 20 , 28 ]. The fusion of these different parts of the CC completes at around GW14, and the CC expands as the brain increases in size [ 29 , 30 ]. Though each region grows at different rates, the overall volume of the CC increases rapidly in early development (GW19–21), and continues to grow at a slower rate until it reaches a plateau at around GW33 [ 29 , 31 , 32 ].…”
Section: Prenatal Development Of Callosal Projectionsmentioning
confidence: 99%